2021
DOI: 10.1016/j.devcel.2020.11.016
|View full text |Cite
|
Sign up to set email alerts
|

NPC1-mTORC1 Signaling Couples Cholesterol Sensing to Organelle Homeostasis and Is a Targetable Pathway in Niemann-Pick Type C

Abstract: Highlights d Proteomic profiling of NPC lysosomes reveals both proteolytic and structural defects d Loss of cholesterol transport activity by NPC1 causes aberrant mTORC1 signaling d mTORC1 inhibition restores lysosomal and mitochondrial function in NPC cells

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 104 publications
11
107
0
Order By: Relevance
“…In support for a causal role between LRH-1 and STARD1, previous reports in human granulosa tumor cells indicated that LRH-1 transactivates the STARD1 promoter through the −105 to −95 site, while targeted loss of LRH-1 in granulosa cells decreased STARD1 mRNA levels and progesterone production in transgenic mice in response to human chorionic gonadotrophin, causing a failure to ovulate [ 43 , 44 ]. Similar to the ability of ACDase to preserve mitochondrial performance despite lysosomal cholesterol storage, recent findings linked lysosomal and mitochondrial dysfunction in NPC disease to mTORC1 hyperactivation [ 45 ]. Interestingly, genetic and pharmacological inhibition of mTORC1 improved mitochondrial function without correcting lysosomal cholesterol accumulation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support for a causal role between LRH-1 and STARD1, previous reports in human granulosa tumor cells indicated that LRH-1 transactivates the STARD1 promoter through the −105 to −95 site, while targeted loss of LRH-1 in granulosa cells decreased STARD1 mRNA levels and progesterone production in transgenic mice in response to human chorionic gonadotrophin, causing a failure to ovulate [ 43 , 44 ]. Similar to the ability of ACDase to preserve mitochondrial performance despite lysosomal cholesterol storage, recent findings linked lysosomal and mitochondrial dysfunction in NPC disease to mTORC1 hyperactivation [ 45 ]. Interestingly, genetic and pharmacological inhibition of mTORC1 improved mitochondrial function without correcting lysosomal cholesterol accumulation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…While multiple cargo receptors are recruited to damaged lysosomes (Figure 4C-E) (Davis et al, 2021;Koerver et al, 2019;Papadopoulos et al, 2017), to date, the cargo receptors critical for linking damaged lysosomes to the core autophagy machinery have not been clearly delineated, although knockdown of SQSTM1 has been reported to result in reduced lysophagic flux (Papadopoulos et al, 2017). We therefore systematically probe cargo receptor involvement in lysophagy.…”
Section: Measurement Of Lysophagic Flux With Lyso-keimamentioning
confidence: 99%
“…In addition, multiple Ub-binding cargo receptors including OPTN, CALCOCO2 and TAX1BP1 are recruited to ubiquitylated bacteria and are required for efficient xenophagy in various contexts (Thurston, 2009a;Thurston et al, 2012;Tumbarello et al, 2015;Wild et al, 2011). While multiple cargo receptors including have been reported to be recruited to damaged lysosomes (Bussi et al, 2018;Davis et al, 2021;Koerver et al, 2019), the underlying mechanisms for recruitment, the identity of the receptors critical for lysophagic flux, and the reasons for the diversity of receptors that are recruited remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…OSBP1-mediated cholesterol transfer from the ER to endolysosomes is increased in NPC1-null cells, resulting in aberrant mTORC1 activation (Lim et al 2019). Pharmacological suppression of mTORC1 signaling can correct several aspects of cellular function independent of the cholesterol storage defect, thus implicating dysregulated mTORC1 signaling as a likely driver of pathology in Niemann-Pick type C (Davis et al 2021). Similarly, another lipid transfer protein ORP1L mediates bidirectional cholesterol transfer between the ER and endolysosomes through interaction with three different ER receptors: VAPA, VAPB, or MOSPD2 (Rocha et al 2009;Zhao and Ridgway 2017;Di Mattia et al 2018;Zhao et al 2020).…”
Section: Contact Sites Involved In Lipid Metabolismmentioning
confidence: 99%